The Tragedy of Corruption - Yefeng Chen; Shuguang Jiang; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2016)
We investigate corruption as a social dilemma by means of a bribery game in which a risk of collective sanction of the public officials is introduced when the number of officials accepting a bribe from firms reaches a certain threshold. We show that, despite the social risk, the pursuit of individual interest prevails and leads to the elimination of honest officials over time. Reducing the size of the groups while increasing the probability of collective sanction diminishes the officials' corruptibility but is not sufficient to eliminate the Tragedy of corruption that leads both firms and officials to earn less than in the absence of corruption.
Keywords: C92; D73; H41; 330; corruption; social dilemma; collective risk; sanction; experiment